Evidence for a critical dose above which damage to carbonate ester bonds in PADC appear after gamma ray and ultra soft X-ray exposures. (May 2020) - Kusumoto, Tamon; Okada, Shogo; Kurashige, Hisaya; Kobayashi, Kazuo; Fromm, Michel; Raffy, Quentin; Ludwig, Nicolas; Kanasaki, Masato; Oda, Keiji; Honda, Yoshihide; Tojo, Sachiko; Groetz, Jean-Emmanuel; et al.
Abstract: It has been confirmed that the density of carbonate ester in poly(allyl diglycol carbonate) (PADC), which is a well-known polymeric nuclear track detector CR-39, begins decreasing above a critical dose of about 60 kGy during exposures to Co-60 gamma rays and Ultra Soft X-rays (USX: K α (Al) with energy 1.49 keV). After exposure to Co-60 gamma rays at 77 K and room temperature (RT), a significant difference in Electron Spin Resonance (ESR) spectra has been observed at both sides of a critical dose of 60 kGy, where is a threshold for the degradation of carbonate ester in PADC. Namely, the types of free radicals in PADC are different from each other below and above this critical dose. Changes in FT-IR spectra of carbonate ester in PADC above critical doses for gamma ray and USX exposures have also been observed, while that of ether decreases linearly with increasing absorbed dose. These results are well concordant with previous results obtained with 28 MeV electron beams. They also indicate that at least two hits of electrons are needed to destroy the carbonate ester in PADC. The layered structure of ion tracks in PADC can be explained thanks to these experimental results. Also, some clues for the identification of created radicals have been obtained from the results using both ESR and IR. Highlights: A significant different ESR signals is observed at both sides of a critical dose. The density of carbonate ester in PADC begins decreasing above a critical dose. Number of electrons and their energies are important for mechanism of latent tracks.